IMPLEMENTING JOB DESCRIPTIONS IN MOSQUE ORGANIZATIONAL STRUCTURES TO SUPPORT ACTIVITY PROGRAMS - Sugiharto; Rafiah Afsah Ramadhani Ramadhani; Faris Faqih; Gendis Ayu Lestari; Ridho Al Rasyid (Jurnal Manajemen Dakwah, 2026)
Mosques play an important role as centers of worship, da'wah, education, and social activity. The diverse implementation of mosque programs requires effective organizational management through a clear division of tasks. This study aims to analyze the implementation of job descriptions within mosque organizational structures and their influence on mosque activity programs. The research employs a library research method by reviewing literature related to mosque management, organizational structure, and job descriptions. The findings indicate that clear job descriptions improve program effectiveness through well-defined task allocation, better inter-departmental coordination, and increased accountability among mosque administrators. Therefore, job descriptions are an important factor in achieving professional and congregation-oriented mosque management.   Keywords: Job Descriptions, Organizational Structure, Mosque Management, Mosque Administrator.